Novel Missense CNTNAP2 Variant Identified in Two Consanguineous Pakistani Families With Developmental Delay, Epilepsy, Intellectual Disability, and Aggressive Behavior - Badshah, Noor; Mattison, Kari A.; Ahmad, Sohail; Chopra, Pankaj; Johnston, H. Richard; Ahmad, Shakoor; Khan, Sher Hayat; Sarwar, Muhammad Tahir; Cutler, David J.; Taylor, Micheal; Vadlamani, Gayatri; Zwick, Michael E.; et al. (Frontiers in Neurology, 2022)
We report the genetic analysis of two consanguineous pedigrees of Pakistani ancestry in which two siblings in each family exhibited developmental delay, epilepsy, intellectual disability and aggressive behavior. Whole-genome sequencing was performed in Family 1, and we identified 80,000 variants located in regions of homozygosity. Of these, 615 variants had a minor allele frequency ≤ 0.001, and 21 variants had CADD scores ≥ 15. Four homozygous exonic variants were identified in both affected siblings: PDZD7 (c.1348_1350delGAG, p.Glu450del), ALG6 (c.1033G>C, p.Glu345Gln), RBM20 (c.1587C>G, p.Ser529Arg), and CNTNAP2 (c.785G>A, p.Gly228Arg). Sanger sequencing revealed co-segregation of the PDZD7, RBM20, and CNTNAP2 variants with disease in Family 1. Pathogenic variants in PDZD7 and RBM20 are associated with autosomal recessive non-syndromic hearing loss and autosomal dominant dilated cardiomyopathy, respectively, suggesting that these variants are unlikely likely to contribute to the clinical presentation. Gene panel analysis was performed on the two affected siblings in Family 2, and they were found to also be homozygous for the p.Gly228Arg CNTNAP2 variant. Together these families provide a LOD score 2.9 toward p.Gly228Arg CNTNAP2 being a completely penetrant recessive cause of this disease. The clinical presentation of the affected siblings in both families is also consistent with previous reports from individuals with homozygous CNTNAP2 variants where at least one allele was a nonsense variant, frameshift or small deletion. Our data suggests that homozygous CNTNAP2 missense variants can also contribute to disease, thereby expanding the genetic landscape of CNTNAP2 dysfunction.